2011
DOI: 10.1158/0008-5472.can-11-0054
|View full text |Cite
|
Sign up to set email alerts
|

Ribonucleotide Reductase Small Subunit M2B Prognoses Better Survival in Colorectal Cancer

Abstract: Ribonucleotide reductase subunit RRM2B (p53R2) has been reported to suppress invasion and metastasis in colorectal cancer (CRC). Here we report that high levels of RRM2B expression is correlated with markedly better survival in CRC patients. In a fluorescence-labeled orthotopic mouse xenograft model, we confirmed that overexpression of RRM2B in non-metastatic CRC cells prevented lung and/or liver metastasis, relative to control cells that did metastasize. Clinical outcome studies were conducted on a training s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 29 publications
1
57
1
Order By: Relevance
“…(27) Details of the de-paraffinization protocol and IHC were described in a previous publication. (28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(27) Details of the de-paraffinization protocol and IHC were described in a previous publication. (28).…”
Section: Methodsmentioning
confidence: 99%
“…Cytoplasmic staining of p53R2 protein was assigned a score from 0 to 2 based on staining intensity (no staining = 0, weakly positive staining = 1, and strongly positive staining = 2) per prior study. (27) The percentage of adenocarcinoma cells stained at each intensity level was recorded for each, resulting in a weighted scores ranged between 0 and 200. For the purposes of statistical analysis, the scores were dichotomized into low p53R2 and high p53R2 based on the median score.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, high p53R2 expression is also a poor prognostic biomarker in non-small cell lung cancer [71] and squamous cell carcinoma [73]. However, some studies have indicated that high p53R2 leads to a better prognosis [74, 75]. Future studies will need to be done on larger patient cohorts to truly determine whether p53R2 expression predicts better or worse patient outcome.…”
Section: Nucleotide Metabolism In Cancermentioning
confidence: 99%
“…To exclude any indirect effects of CEA on angiogenesis such as previously reported CEA binding to NK cells via CEACAM1 (22), we next performed tumor transplants in NSG mice, which are characterized by severe immunodeficiency due to the absence of functional NK cells, absence of mature T and B cells, and deficiency in cytokine signaling (34). As expected, growth of tumor transplants was enhanced in both groups, but CEA-expressing tumors (Meth-A/CEA) grew significantly faster than Meth-A/wt.…”
Section: Cea Overexpression Is Accompanied By Enhanced Tumor Vascularmentioning
confidence: 99%